`We help them, and they help us': Reciprocity and relationality in Chinese aid to Africa - Marina Rudyak (Journal of International Development, 2022)
This paper applies Marcel Mauss' Gift Theory in conjunction with Qin Yaqing's Relational Theory to Chinese foreign aid. It proposed that this approach allows to conceptualise Chinese aid to Africa as a continuous gift cycle initiated in Bandung and has been going uninterrupted till today. The paper argues through the language of reciprocity and relationality, China symbolically affords the recipient status in a way that Northern aid does not. The real existing power asymmetries between China and Africa do not per se translate into unlimited influence as China can never be sure of reciprocity and is obliged to keep giving continuously.
Keywords: 300; Africa; aid; China; development; development cooperation; Gift Theory; international relations; Relational Theory